2006
DOI: 10.1111/j.1745-7262.2006.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistopathology of the contralateral testis of rats undergoing experimental torsion of the spermatic cord

Abstract: Experimental spermatic cord torsion induces, in the contralateral testis, a focal damage of seminiferous tubules characterized by apoptosis and sloughing of germ cells. Results suggest humoral and cellular immune mediated testicular cell damage in which macrophages and mast cells seem to be involved in the induction of germ cell apoptosis through the TNF-alpha/TNFR1 system and in the modulation of the inflammatory process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 17 publications
1
31
2
Order By: Relevance
“…Recently, knowledge of the expression of various cytokine receptors in the testis has increased [42][43][44]. In our next study, we will investigate the expression of intratesticular cytokine receptors through gene and proteomics experiments on intracellular cytokine receptors in both normal and EAO-affected testes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, knowledge of the expression of various cytokine receptors in the testis has increased [42][43][44]. In our next study, we will investigate the expression of intratesticular cytokine receptors through gene and proteomics experiments on intracellular cytokine receptors in both normal and EAO-affected testes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that IL-1α mRNA was detected in Sertoli cells and Leydig cells and that IL-1β mRNA was detected in Leydig cells [39][40][41]. Investigation into the localizations of these cytokines may help to explain immunological mechanism of EAO.Recently, knowledge of the expression of various cytokine receptors in the testis has increased [42][43][44]. In our next study, we will investigate the expression of intratesticular cytokine receptors through gene and proteomics experiments on intracellular cytokine receptors in both normal and EAO-affected testes.…”
mentioning
confidence: 99%
“…This is consistent with the current findings that the spermatogonia are the primary cells that are affected. In contrast, another researcher observed that the exfoliated sloughed germ cells were spermatocytes and spermatids [44].…”
Section: Discussionmentioning
confidence: 93%
“…Burukoğlu and Bayçu [10] observed several congested thickened blood vessels and homogeneous oedematous material in the interstitium which is infiltrated by different cells such as leukocytes and macrophages. The thickened blood vessel wall and oedema are due to cytokines secreted by macrophages situated in the peritubular zones [1,44].…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez et al [11] studied the immunohistopathological changes in the contralateral testis of rats after spermatic cord torsion, and the results suggested humoral and cellular immune-mediated testicular cell damage of the contralateral testis. Salman Table 2.…”
Section: Discussionmentioning
confidence: 99%